High Toxoplasmosis Seroprevalence and Anemia Among Early-Mid Pregnant Women in Jember, Indonesia - Wulandari, Lindi Priyantika Tri; Armiyanti, Yunita; Aziz, Ayu Munawaroh; Hermansyah, Bagus; Sulistyaningsih, Erma; Utami, Wiwien Sugih (Journal of Community Medicine and Public Health Research, 2025)
Toxoplasmosis is an infection caused by the parasite Toxoplasma gondii, which can be transmitted through various routes. Toxoplasmosis in pregnant women may cause abortion and fetal disabilities. Decreased body immunity due to anemia can increase the risk of toxoplasmosis during pregnancy. The purpose of this study was to identify the characteristics of pregnant women and their association with anemia, determine the prevalence of anemia and toxoplasmosis infection in pregnant women, and investigate whether anemia is a risk factor for toxoplasmosis in pregnant women. This research is an analytical, observational study using a cross-sectional laboratory examination. The sample in this study consisted of blood collected from first- and second-trimester pregnant women at the Kaliwates and Banjarsengon Public Health Centers for hemoglobin analysis and toxoplasmosis serology. Accidental sampling was conducted from July to December 2024. The research data were presented in tabular form and analyzed using the Chi-square test. This study was conducted on 65 pregnant women. The number of pregnant women with anemia was 43% and the number of pregnant women who were positive for toxoplasmosis was 66%. A significant association exists between gestational age and anemia (p-value = 0,041). Bivariate analysis between anemia and T. gondii infection showed no significant association (p-value = 0.182). This study concludes that anemia is not proven to be a risk factor for toxoplasmosis infection in pregnant women. However, the cases of anemia and toxoplasmosis were high and require specific attention.